Quelle éthique pour quelle Église ? - Collaud, Thierry 1957- (2025)
On the occasion of his farewell lecture, the author looks back at his approach to ethics, which has led him to reflect on the way in which the Catholic Church should express its morality, less as a normative discourse than as a way of presenting itself as a fraternal community, the Body of Christ. Seeking the good life of the Church means trying to describe its virtues, and we have chosen three of them: 1) Coherence, which is thought of in musical terms as polyphony developing around the axis of a cantus firmus. 2) Habitation, which describes the just relationship to the place between the insufficiency of an uninvolved presence and the excess of unwarranted appropriation. 3) Finally, humility as self-emptying which becomes the virtue that allows grace to shine through and makes the Church beautiful and gracious.
À l’occasion de sa leçon d’adieu, l’auteur revient sur son approche de l’éthique qui l’a conduit à réfléchir sur la façon dont l’Église catholique devrait donner à voir sa morale, non pas tant sous forme de discours normatif, mais comme manière de se présenter comme communauté fraternelle Corps du Christ. Chercher la vie bonne de l’Église, c’est tenter d’en dire les vertus, on en a choisi trois : 1) La cohérence qui est pensée en termes musicaux comme polyphonie se déployant autour de l’axe d’un cantus firmus. 2) L’habitation qui dit le juste rapport au lieu entre le trop peu d’une présence non impliquée et le trop d’une appropriation indue. 3) Finalement l’humilité comme dépouillement qui devient la vertu qui laisse transparaître la grâce et rend l’Église belle et gracieuse.
Keywords: harmonie; hospitalité; humilité; Morale; Vertus; Église